Abdominal Adhesion Prevention: Still a Sticky Subject - Lauder, Chris I.W.; Garcea, Giuseppe; Strickland, Andrew; Maddern, Guy J. (Digestive surgery, 2010)
Background: Adhesion formation remains an almost inevitable consequence of abdominal procedures, potentially resulting in significant morbidity and mortality. There is an ongoing need to evaluate current understanding of adhesion formation and products aimed at prevention. Failure to keep up to date with adhesion treatment may subject clinicians to a greater medico-legal risk. Design: Review of published studies exploring the problem of peritoneal adhesion formation. This encompasses the underlying processes of adhesion formation combined with general approaches to reduce formation. An overview of products trialled to prevent formation in both the animal model and clinical setting describes products of scientific interest and commercial success. Results: Advances in surgical technique, such as laparoscopic surgery, can help minimize the probability of adhesion formation. Currently barrier products, whilst reducing adhesion formation, have not been shown to reduce the risk of readmission with complications related to adhesions. Hybrid products may improve upon this situation. Conclusions: No single approach has been wholly satisfactory in reducing adhesions. Research into the processes driving adhesion formation is providing exciting new targets for therapeutic agents. It would seem plausible that with many promising avenues of research a revolutionary agent to reduce the incidence of adhesional small bowel obstruction may result.